Experimental study on impulse waves generated by gravitational collapse of rectangular granular piles - Huang, Bolin; Zhang, Quan; Wang, Jian; Luo, Chaolin; Chen, Xiaoting; Chen, Lichuan (Physics of fluids (1994), 2020)
Towering in many gorges of reservoirs and coastal zones, pillar rock masses may collapse and fall due to foundation crushing, and the impact on water by debris leads to impulse waves. In this study, the process of impulse wave induction by the gravitational collapse of granular piles was investigated using particle image velocimetry. The experimental results showed that the collapse process of partially submerged particles was significantly different from that of dry particles. Near the water surface, particles moved outward in a reversed “S” shape. In the presence of water at the slope foot, the time and the distance traveled by the particles were reduced. The hydraulic effects such as water entrainment, vortex, rolling, and viscous drag exacerbated the energy dissipation of the granular piles, thus reducing particle mobility. Thirty five experiments suggested that the impulse waves induced by granular piles could be categorized as bores, solitary waves and nonlinear transition waves according to the functional inequality, which consisted of the aspect ratio and the relative thickness. The fitted formula for the run-out of partially submerged granular piles and the corresponding maximum wave amplitudes was derived by nonlinear regression of the experimental data. In comparison with previous formulas, these formulas are power functions consisting of aspect ratio and relative thickness and are highly suitable for predicting the collapse of granular piles and the impulse waves induced as the correlation coefficients of calculated results by these formulas and the measured values exceeded 0.93.